Quantification of C-type lectin gene expression during hyperinfection in strongyloidiasis - Al-Zihiry, Khalid Jameel Kadhim; Abdulhaleem, Noor; Atshan, Salman Sahab; Kadhim, Amal Jameel; Ibraheem, Zaid Osamah; Unyah, Ngah Zasmy (Medknow Publications, 2020)
Strongyloides stercoralis is the intestinal nematode in humans, and it infects millions of people worldwide but thrives in warm countries with poor sanitation conditions. Clinical manifestations of the infection may range from asymptomatic to chronic. Strongyloides cause hyperinfection syndrome and dissemination in individuals with impaired cell-mediated immunity due to its ability to proliferate within the host that may increase the mortality rate up to 87%. The diagnosis of hyperinfection syndrome is difficult to establish and entails a high level of suspicion. The objective of the present study was to measure the expression level of C-type lectin gene coding to protein biomarker candidates from the excretory/secretory (ES) products of the infective filariform larva that can be used as diagnostic indicators for early hyperinfection syndrome in strongyloidiasis. An experimental study was carried out to induce hyperinfection of L3 larvae of S. ratti in experimentally immunosuppressed Wistar rats using prednisolone, a corticosteroid immunosuppressive drug. Prednisolone treatment resulted in a significant increase in the parasitic intensities. Relative semi-quantitative real-time PCR was performed to compare the expression level of the C-type lectin’s gene between treated and nontreated groups with this drug. C-type lectin gene showed significantly higher expression levels in the treated samples. The study concluded that C-type lectin expression level was successfully measured and could be used as a diagnostic biomarker during early hyperinfection syndrome in strongyloidiasis.